Análise do processo de retificação interna aplicado à fabricação de bicos injetores diesel - Bilha, Vitor Meira (2015)
Industries of manufactured products have increased their efficiency optimizing the natural resources usage and Diesel commercial vehicles are included in this scenario. For Diesel engines, one of the most important components of the injection system is the nozzle injector. In Brazil, EURO5 legislation was recently introduced, bringing new emission limits for Diesel engines. Because of this, the nozzle injector design has changed and some manufacturing tolerances were reduced, in special the body seat geometry. This also changed the nozzle opening pressure. In this new process, the body seat grinded conical surface impacts on this functional parameter and consequently the Diesel engine performance. This study has as target to analyze a recurrent defect in the internal conic grinding process of the nozzle body seat. A trial was performed in this process according to Taguchi method and signal / noise ratio for 2D topographic parameters were defined. The body seat surface was also analyzed using 3D topographic analysis. The results of this study include the possible cause of the recurrent failure, characterization of the ground surface, process main elements integrity assessment and optimization of the grinding process parameters.